Fragmentation Functions for Light and Heavy Quarks in Simulated Proton-Proton Collisions - Sadoun, Nermin Kamal (AUC Knowledge Fountain, 2025)
In the first microsecond after the Big Bang, the early universe is believed to have been in an excited state known as the Quark-Gluon Plasma (QGP) state, a state of free quarks and gluons. Conducted experiements, like Heavy-ion collisions at the Relativistic Heavy Ion Collider (RHIC) and the Large Hadron Collider (LHC), have showed some evidences of the formation of this extreme states in the collisions. Jet quenching and elliptic flow are two phenomena that provide significant evidence for the creation of QGP and its distinctive characteristics. Although the major framework for studying QGP is still heavy-ion collisions, new research indicates that, under some circumstances, small collision systems like proton-proton (p-p) and proton-nucleus (p-A) collisions may also show QGP-like effects. Using the PYTHIA event generator as a theoretical baseline, this work creates a baseline for researching such effects in p-p collisions. In order to study non-collective phenomena in small systems, PYTHIA is an idealized reference that replicates particle generation in a vacuum without medium effects. This thesis analyzes near-side and away-side particle yields, azimuthal correlations, and the nuclear modification √ factor IAA for π 0 and J/ψ triggers in p-p collisions at s = 13 TeV, with data generated using PYTHIA. The dependence of these observables on particle multiplicity, transverse momentum thresholds, and fragmentation variables provides detailed insights into the contrasting behavior of soft (π 0 ) and hard (J/ψ) fragmentation processes. Comparisons across different multiplicity classes and passoc thresholds highlight the distinct sensitivity of π 0 to background effects and the T relative stability of J/ψ yields in high-multiplicity environments. This work provides a useful reference for understanding experimental data and identifying possible signatures of QGP in small systems by imposing additional constraints on the extracted measured observables and establishing a baseline for azimuthal correlations and yield distributions in p-p collisions.